Hands on a clinical companion : steps to confidence in musculoskeletal diagnosis - Browning, Simon (Tfm Pub., 2004)
A companion to aid diagnostic process of musculoskeletal injuries or disorders. aimed at osteopaths, chiropractors, orthopaedic medical practitioners and physicians.